Degrees of disadvantage - Chinmayi Srikanth (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This study is positioned in two strands of literature-intersectionality and social mobility. It is the first to measure (dis)advantage at the individual level as an outcome of the intersectionality of identities and parental circumstances. By linking circumstances at the parental level with (dis)advantage at the individual level, this study uses fuzzy-set Qualitative Comparative Analysis (fsQCA) in an unprecedented application, i.e. to study social mobility or generational persistence. By accounting for intersectional ascribed identities, this study is also the first to analyse social mobility for the intersectionality of caste, religion, and gender identities. Using data from the India Human Development Survey 2011-12, the study finds that, in a given generation, Hindu women can observe high outcomes only if they are born into advantageous parental circumstances. This is further tempered by their position in the social hierarchy. For men, advantageous circumstances are not a necessary precondition for upward mobility. By building epistemological arguments, this paper also makes a contribution by being the first to contend that fsQCA is the ideal method to study overdeterministic social science phenomena.
Keywords: A12; B51; J15; J62; 330; intersectionality; social mobility; caste; gender; India; overdeterminism